An assessment of the influence of CCAFS' climate data and tools on outcomes achieved 2010-2016 - Rassmann, Kornelia; Schuetz, Tonya (2017)
These four volumes comprise an evaluation report commissioned by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). The evaluation was undertaken by the independent evaluators Kornelia Rassmann and Tonya Schuetz and supported by the CCAFS internal evaluation team led by Philip Thornton and Laura Cramer. It mainly used Outcome Harvesting (OH) but also elements from Impact Pathway thinking and Contribution Analysis to describe and analyze ‘development outcomes’ that were directly or indirectly influenced by one of three CCAFS’ climate products – the GCM Climate Portal, MarkSimGCM, and the Climate Analogues tool. Volume 1 is the main evaluation report. Volume 2 presents survey results and user perspectives. Volume 3 contains outcome stories. Volume 4 has definitions of terms and the coding book used during the evaluation.